AI AS A MEDIUM IN CONCEPTUAL ART PRACTICE - Gupta, Dr. Peeyush Kumar; Ankayarkanni B; Kumar, Amit; Dhiman, Kuldeep; Jain, Romil; Pawar, Amrut Ramchandra; Dixit, Dipti Nitin (ShodhKosh: Journal of Visual and Performing Arts, 2025)
This paper sets out to review the advent of artificial intelligence as an important medium in modern conceptual art practice, with particular reference to its ability to both extend and confuse the traditional operating assumption of ideas being the primary element in conceptual art practice. The study is based on the historical development of conceptualism, starting with the early linguistic and systemic arts and moving to the subsequent computational experimentalism, which orients AI to a tradition of artistic and process-oriented approaches, in which processes, instructions, and networks of meaning take the place of conventional object-based production. The distinctive language, image, and symbolic manipulatory skills of AI present new forms of authorship, autonomy, and indeterminacy and provide artists with the opportunity to create works that predetermine system-directed meaning, algorithmic patterning, and computational aesthetics. By presenting the history of algorithmic practices and the current case study, the paper will show that AI is not only a technical tool but also an active conceptual agent that can act to construct the propositions of art. This incorporates its role as partner, actor, and even proxy author, and leads to a rethinking of the agency of the creative and agency, and purposefulness. The theoretical consequences of the changes throw down challenges to the accepted versions of interpretation, work of art, and the limits of the intelligent in the artistic frames. Finally, the paper concludes that AI has a transformative potential to conceptual art that relates to the possibility of producing novel types of ideas, speculative questions, and bringing immaterial ideas to life.